P107 IL10 secretion endows intestinal human iNKT cells with regulatory functions towards pathogenic T lymphocytes in Crohn's disease patients. (21st January 2022) - Burrello, C; Strati, F; Diaz-Basabe, A; Lattanzi, G; Lopez, G; Trombetta, E; Conforti, F S; Botti, F; Vecchi, M; Fantini, M C; Caprioli, F; Facciotti, F
Abstract: Background: I nvariant Natural Killer T (iNKT) cells perform pleiotropic functions in different tissues by secreting a vast array of pro-inflammatory and cytotoxic molecules. However, the presence and function of human intestinal iNKT cells capable to secrete immunomodulatory molecules such as IL-10 has never been reported so far. Here we describe for the first time the presence of IL10-producing iNKT cells (NKT10 cells) in the intestinal lamina propria of healthy individuals and of Crohn's Disease (CD) patients. Methods: Frequency and phenotype of NKT10 cells were analyzed ex-vivo from intestinal specimens of Crohn's disease (n=17) and controls (n=7). Stable CD-derived intestinal NKT10 cell lines were used to perform in vitro suppression assays and cocultures with patients'-derived mucosa-associated microbiota. Experimental colitis models were performed by adoptive cell transfer of murine splenic naïve CD4+ T cells in the presence or absence of IL10-sufficient or deficient iNKT cells. In vivo induction of NKT10 cells was performed by administration of SCFA by oral gavage. Results: Patient's derived intestinal NKT10 cells demonstrated suppressive capabilities towards pathogenic CD4+ T cells. The presence of increased proportions of mucosal NKT10 cells associated with better clinical outcomes in CD patients. Moreover, an intestinal microbial community enriched in SCFA-producing bacteria sustained the production of IL10 by iNKT cells. Finally, IL10- deficient iNKT cells failed to control the pathogenic activity of adoptively transferred CD4+ T cells in an experimental colitis model. Conclusion: These results describe an unprecedent IL10-mediated immunoregulatory role of intestinal iNKT cells in controlling the pathogenic functions of mucosal T-helper subsets and in maintaining the intestinal immune homeostasis.